Sporadic Burkitt lymphomas of children and adolescents in Chinese: a clinicopathological study of 43 cases - Bi Cheng-Feng; Tang Yuan; Zhang Wen-Yan; Zhao Sha; Wang Xiao-Qing; Yang Qun-Pei; Li Gan-Di; Liu Wei-ping (BMC, 2012)
Abstract Background To investigate the clinical and pathologic features as well as the MYC translocations of childhood Burkitt lymphoma (BL) from China. Methods Fourty-three cases of childhood BL were retrospectively investigated in morphology, immunophenotype, genotype, treatments and survival analysis. Results Clinically, there was a marked male predominance in sex distribution (M: F = 9.75:1); abdomen was the most frequent extranodal sites of involvement (46.5 %), followed by jaws and facial bones (16.3 %). Two third of the patients were in stageI ~ II. Morphologically, 69.76 % of the cases showed classical histologic features, while 30.24 % of them showed greater nuclear pleomorphism in size and shape. Five cases (11.6 %) were positive for EBER1/2. Thirty-one of the 40 cases (77.5 %) had the aberration of IGH/MYC translocation while 7 (17.5 %) had non-IGH/MYC translocation. Thirty patients (69.7 %) received operation and/or chemotherapy while 13 patients (30.3 %) received no treatment. Twenty-seven patients (62.8 %) died of the tumor, 16 alive, with the average survival time 4.9 and 48.7 months respectively. High IPI, advanced clinical stage, increased serum level of LDH and no chemotherapy received as well as tumor size ≥10 cm were related to the lower survival rates of the tumor. Conclusions Several differences were showed in this group of BL, including a much higher ratio of male patients, more cases in stageII, clinically inconsistent treatment and a very poor outcome. Virtual slides The virtual slide(s) for this article can be found here http://www.diagnosticpathology.diagnomx.eu/vs/1552295877710135